Контроль прийняття рішень у точці біфуркації в процесі перебігу підприємницької діяльності - Хома, І. Б. (Видавництво Львівської політехніки, 2015)
Сформовано та деталізовано системний підхід щодо запровадження контролю прийняття рішень у точці біфуркації в умовах перебігу підприємницької діяльності. Визначено властивості точки біфуркації в синергетичній концепції хаосу та побудовано узагальнений поетапний процес виходу з цієї точки з виокремленням елементу введення додаткового контролю прийнятого рішення для перевірки його оптимальності в діапазоні подолання невизначеності та випадкових економічних дій. The systematic approach for the control’s introduction of decision-making at the bifurcation point in the conditions of the course of enterprise activity is generated and detailed. The properties of bifurcation point in a synergetic concept of chaos are determined and the summarized stage-by-stage process of exit from this point is built with the emphasis of introduction’s element of the additional control of the accepted decision as a check on its optimality in the range to overcome uncertainty and occasional economic activities. The incorrect decision at the bifurcation point can substantially alter the development of entrepreneurial activity, since at this point due to the capability of multidirectional decision making, they can be wrong and totally unjustified for expected calculations, and their implementation does not allow in a fairly limited time interval to come to a common optimal results. Therefore the problem of early warning of non-optimal decision in the moment of overcoming of bifurcation point in the business through the introduction of additional effective control of decision-making is topical. The bifurcation point is a critical state of any system in which the available system becomes unstable towards to all changes those occur intermittently. Besides, the uncertainty regarding the future development of the entire system occurs at the bifurcation point, and itself state of the system is characterized by randomness and absolute unpredictable. The complexity of the validation of the accepted decision at the bifurcation point, as it is known, depends on such properties: the nonclosure of economic systems, in the context of which is being held enterprise activity; the disequilibrium of economic processes, that complicates the use of economic and mathematical modeling; the irreversibility of economic evolution; the nonlinearity of economic transformation; the ambiguity of economic goals; the presence of the inevitable bifurcation choice. The identification of the bifurcation point by its coordinates states a fact of the specific overcoming chaotization and demands the immediate going out of this condition through the choice of concrete decision, as well as this allows to establish the existence of the bifurcation model for further development of entrepreneurial activity, which, in contrast to the evolutionary model of development, will be based on a obligatory change of system’s quality. The problem of the complexity of the passage of this point consist the possibility of a wide choice of decision-making, where each vector direction is rationally correct and, besides, what the final decision will be taken, it is impossible to predict in advance. It is also possible and alternative decisions, which require pre-evaluation with respect to the other. The process’ introduction of way out of the bifurcation point in enterprise activity with elements of input of additional control of the optimum decision-making not only allows to systematize approach to the effective control of decision-making at this point, but also studies have shown that to save financial resources and to minimize the cost of the search for measures to stabilize the situations which arise at wrongly economic decision-making in any case.
Control of decision-making at bifurcation point in course of enterprise activity
Keywords: підприємницька діяльність; точка біфуркації; контроль прийняття оптимальних рішень; концепція хаосу; enterprise activity; bifurcation point; control of optimal decision-making; concept of chaos